2015
DOI: 10.1186/s12906-015-0705-5
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Laughter Yoga therapy for haemodialysis patients: a pre-post intervention feasibility study

Abstract: BackgroundLaughter Yoga consists of physical exercise, relaxation techniques and simulated vigorous laughter. It has been associated with physical and psychological benefits for people in diverse clinical and non-clinical settings, but has not yet been tested in a haemodialysis setting. The study had three aims: 1) to examine the feasibility of conducting Laughter Yoga for patients with end stage kidney disease in a dialysis setting; 2) to explore the psychological and physiological impact of Laughter Yoga for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
2
46
0
2
Order By: Relevance
“…()showed a nonsignificant reduction in depressed mood, whereas Bennett et al. 's () study reported a nonsignificant increase in depressed mood immediately postintervention.…”
Section: Results Of Individual Studiesmentioning
confidence: 88%
See 2 more Smart Citations
“…()showed a nonsignificant reduction in depressed mood, whereas Bennett et al. 's () study reported a nonsignificant increase in depressed mood immediately postintervention.…”
Section: Results Of Individual Studiesmentioning
confidence: 88%
“…Six studies (Bennett et al., ; Ellis, Ben‐Moshe, & Teshuva, ; Farifteh et al., ; Shahadi et al. 2010; Weinberg, Hammond, & Cummins, ; Yazdani, Esmaeilzadeh, Pahlavanzadeh, & Khaledi, ) met the criteria for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes were calculated using G-Power version 3.1 (Franz, Universitat Kiel, Germany), using an alpha value of 0.05 and a power of 80%. 5) All results are given as the mean ± standard deviation, and significance was set at P<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis nurses should therefore be encouraged to increase people with CKD's happiness through the integration of laughter yoga [37], the Fordyce's happiness program [38], and the visualization of humor ilms [39], during dialysis sessions. This intervention will improve both people with CKD's wellbeing and health outcomes, such as quality of life, afect, and depressive symptoms.…”
Section: Implications For Practicementioning
confidence: 99%